143 Metabolic control of nutrient metabolism and milk synthesis in bovine mammary epithelial cells. - Burgos, S (J Anim Sci, 2018)
Fluctuations in nutrient and energy supply to the mammary gland have a profound influence on milk yield and composition. These effects have been traditionally explained solely from the standpoint of nutrients serving as substrates for synthesis of milk components. However, we now know that nutrients can also be sensed by signal transduction pathways that relay information on nutrient sufficiency to the cell’s metabolic machinery. The mechanistic target of rapamycin complex 1 (mTORC1) has emerged as a central nutrient-sensing pathway that integrates information on amino acid availability, cellular energy status, and insulin levels (an indicator of organismal energy status) to control a multitude of catabolic and anabolic cellular processes. Recent studies have begun to explore the role of the mTORC1 pathway in the control of nutrient metabolism and milk component synthesis in bovine mammary epithelial cells. These studies have revealed that the supply of individual essential amino acids can activate mTORC1 to regulate the synthesis of milk proteins through phosphorylation of downstream targets involved in mRNA translation. The availability of energy yielding substrates for bovine mammary cells can also influence mTORC1 activity, at least in part through modulation of 5’ adenosine monophosphate-activated protein kinase activity. In addition, insulin activates mTORC1 through the phosphatidylinositol-4,5-bisphosphate 3-kinase pathway, but its role in regulation of milk component synthesis is less well-established. Emerging evidence also implicates mTORC1 in the control of lipogenic gene expression through regulation of sterol regulatory element-binding transcription factor 1 function, a master regulator of de novo lipid synthesis. Less is known about the potential role of mTORC1 in regulation of glucose metabolism in mammary cells. A better understanding of the role of mTORC1 in the control of mammary nutrient metabolism could lead to more efficient use of nutrients for milk component synthesis.